Comparison of Long-Term Survival of Patients with Solitary Large Hepatocellular Carcinoma of BCLC Stage A after Liver Resection or Transarterial Chemoembolization: A Propensity Score Analysis - Zhu, Shao-Liang (PLoS One, 2014)
BACKGROUND: The aim of this study was to compare the long-term outcome of patients with a solitary large (>5 cm) hepatocellular carcinoma (HCC) in Barcelona Clinic Liver Cancer (BCLC) stage A who received liver resection (LR) or transarterial chemoembolization (TACE). METHODS: Our study examined 128 patients treated by LR and 90 treated by TACE. To reduce bias in patient selection, we conducted propensity score analysis in the present study and 54 pairs of patients after propensity score matching were generated, their long-term survival was compared using the Kaplan–Meier method. Independent predictors of survival were identified by multivariate analysis. RESULTS: Long-term survival was significantly better for the LR group by log-rank test (P<0.001). In multivariate analysis, tumor size, serum ALT level and TACE independently predicted survival. Despite similar baseline characteristics after propensity score matching, LR group still had significantly better survival (1 year, 68.5 vs. 55.0%; 3 years, 47.6 vs. 21.2%; 5 years, 41.3 vs. 18.5%; P = 0.007) than TACE group. The LR and TACE groups had comparable 30- and 90-day post-treatment mortality. Multivariate analysis showed that serum ALT level, serum AFP level and TACE independently predicted survival by multivariate analysis after propensity score matching. CONCLUSION: Our propensity-score-matched study suggested that LR provided significantly better long-term survival than TACE for a solitary large HCC of the BCLC stage A, regardless of tumor size.